Diseño de la gestión de colocación de créditos por libranza en empresas de externalización de asesorías financieras (2015)
In this paper an existing problem arises in the process of placement of loans by warrant in outsourcing companies of financial services. We proceed to present the problem characterization of such organizations and their current operating model. Subsequently, a proposed process management with the methodology of process modeling Business Process Management (BPM) supported in the design of an information system model is proposed and finally a case study where it was implemented presents the proposed model supported the development of a prototype system developed information in the language Visual Basic for Applications in Microsoft Excel 2010.